APPLYING RISK ADJUSTED COST‐EFFECTIVENESS (RAC‐E) ANALYSIS TO HOSPITALS: ESTIMATING THE COSTS AND CONSEQUENCES OF VARIATION IN CLINICAL PRACTICE. (30th April 2012) - Karnon, Jonathan; Caffrey, Orla; Pham, Clarabelle; Grieve, Richard; Ben‐Tovim, David; Hakendorf, Paul; Crotty, Maria
ABSTRACT Cost‐effectiveness analysis is well established for pharmaceuticals and medical technologies but not for evaluating variations in clinical practice. This paper describes a novel methodology—risk adjusted cost‐effectiveness (RAC‐E)—that facilitates the comparative evaluation of applied clinical practice processes. In this application, risk adjustment is undertaken with a multivariate matching algorithm that balances the baseline characteristics of patients attending different settings (e.g. hospitals). Linked, routinely collected data are used to analyse patient‐level costs and outcomes over a 2‐year period, as well as to extrapolate costs and survival over patient lifetimes. The study reports the relative cost‐effectiveness of alternative forms of clinical practice, including a full representation of the statistical uncertainty around the mean estimates. The methodology is illustrated by a case study that evaluates the relative cost‐effectiveness of services for patients presenting with acute chest pain across the four main public hospitals in South Australia. The evaluation finds that services provided at two hospitals were dominated, and of the remaining services, the more effective hospital gained life years at a low mean additional cost and had an 80% probability of being the most cost‐effective hospital at realistic cost‐effectiveness thresholds. Potential determinants of the estimated variation in costs and effects were identified, although more detailed analyses to identify specific areas of variation in clinical practice are required to inform improvements at the less cost‐effective institutions. Copyright © 2012 John Wiley & Sons, Ltd.